Environmental Acts and Regulatory Agencies Affecting Citrus Groves in Florida - Michael T. Olexa; Brian J. Boman; Scott L. Hall (EDIS)
This is document No. CH161 and Circular 1423, one of a series of the Agricultural and Biological Engineering Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: September 2002.